IDENTIFICATION OF LOCAL WISDOM IN COMMUNITY CULTURE IN DANAU SENTARUM NATIONAL PARK - Siti Rabiatun Agustini; Deva Fosterharoldas Swasto (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2023)
Cultural diversity spans from Sabang to Merauke with a variety of local wisdom. One is on the island of Borneo, especially in West Kalimantan Province. An area with a variety of very rare ecosystems and local cultural wisdom that has existed for generations is the Danau Sentarum National Park (TNDS) area which has two types of local cultural wisdom of the local community, namely the Malay tribe and the Dayak tribe. The purpose of this research is to identify the characteristics of local wisdom on culture in Danau Sentarum National Park with a case study in Batang Lupar District, Kapuas Hulu Regency, West Kalimantan Province. This research used qualitative research methods. Data were collected through interviews, field observations, and document review. Sampling used the purposive sampling method. Data analysis techniques used qualitative descriptive analysis. The results of this study found that the local wisdom of the Danau Sentarum area community from the Malay tribe community and the Dayak tribe community has much uniqueness in its culture and has customary rules that have been carried out for generations to regulate the lives of people who are in the Danau Sentarum National Park area. The forest area and Danau Sentarum are a very important part of the lives of the people who live in the area, so they must be protected and managed together with the guardians and managers of the forest, namely local and traditional communities.